(3MGTjI Ydi bSe GdefWb ef GdJgPjH ddJaJGRGfjs - (3GdSYjOj, GdCQOHjdj, eMeO Hf Cejf, J (B950 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi JgPjH GdefWb hGdcdGe hHYO agPg JYdjbGJ Ydi bSe GdefWb ef GdJgPjH CJhSd HgG Edi fXQI ef MVQI SdWGf HdGO GdEjeGf CHh GdZGRj NGf HgGOQNGf GdMSjfjs
(3BNQgG (B:s
(3aGdXGgQ Cf jbGd chf GdTjA HMjK jdRe ef GdYde Hg GdYde dTjA BNQ ceG gh GdeTghQ aj gPG GdebGe hdYdg GNJGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/5793 / 142s
(3cTa GdXfhf (B1/ 516s
(3gOjI GdYGQajf (B2 / 207s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs